Poemas liminales entre Occidente y Oriente: una aproximación a El olmo incierto de la nevada (1930) de Pedro Zulen - Pelaez Sagastegui, Elizabeth (2025)
The paper analyzes four poetic texts selected from El olmo incierto de la nevada, posthumous collection of poems by Pedro Salvino Zulen Aymar (1889-1925), published in 1930 in Lima, by Chenyek printing press, with the respective authorization of Dora Mayer. These texts are «El olmo incierto de la nevada» (poetic prose), the poems «El poema sin nombre», «El poema de una lágrima» and «Humano fragor», in order to propose that Pedro Zulen’s poetic produc-tion is in a liminal state between the western and the eastern, terms that I use to explain how both are amalgamated in the posthumous collection of poems by Zulen. The western is suggested by references to Romanticism (18th-19th centuries), Modernism (19th-20th centuries) and the Spanish-American Vanguard (mid-20th century), while the eastern by references to Eastern-born religious and philosophical systems such as zen buddhism and taoism, to the ancient chinese tree Ginkgo biloba, as well as to kigo and mono no aware, the latter concepts inherent in the japanese short poem known as haiku.